Sequential mutations in hemagglutinins of influenza B virus isolates: definition of antigenic domains. - Krystal, M (1983)
Comparative analysis of the amino acid sequences of hemagglutinins (HAs) of influenza B/Lee/40, B/Md/59, and B/HK/73 viruses has allowed examination of the molecular basis of antigenic variation in type B viruses. As seen with influenza type A viruses, antigenic drift in influenza B viruses proceeds mostly through the accumulation of amino acid substitutions within the HA1 portion of the HA molecule. However, the rate of variation observed among the influenza B virus HAs appears to be significantly lower than the observed rate of variation among influenza A virus HAs. The overall rate of amino acid change in the HA1s of the influenza B viruses studied is 2% per 10 years, whereas the HA1s of H3 influenza A viruses vary by 9.2% per 10 years. The sequences of the influenza B HAs were also examined in relation to the three-dimensional model for the A/Aichi/2/68 HA. When the primary amino acid sequences are compared, it appears that most of the important structural features of the type A HAs--such as the sialic acid binding site, the disulfide linkages, and the stem structure of the trimer--are conserved in the influenza B virus HAs. Regions are also identified where extensive amino acid substitutions have occurred among the three antigenically distinct influenza B virus HAs. The locations of these areas in the B HA structure correspond to antigenic regions proposed for the A virus HAs. In addition, modulation of antigenic regions in B virus HAs may also occur through amino acid deletions and variation in glycosylation sites.